Graphene devices based on laser scribing technology. (22nd February 2018) - Qiao, Yan-Cong; Wei, Yu-Hong; Pang, Yu; Li, Yu-Xing; Wang, Dan-Yang; Li, Yu-Tao; Deng, Ning-Qin; Wang, Xue-Feng; Zhang, Hai-Nan; Wang, Qian; Yang, Zhen; Tao, Lu-Qi; et al.
Abstract: Graphene with excellent electronic, thermal, optical, and mechanical properties has great potential applications. The current devices based on graphene grown by micromechanical exfoliation, chemical vapor deposition (CVD), and thermal decomposition of silicon carbide are still expensive and inefficient. Laser scribing technology, a low-cost and time-efficient method of fabricating graphene, is introduced in this review. The patterning of graphene can be directly performed on solid and flexible substrates. Therefore, many novel devices such as strain sensors, acoustic devices, memory devices based on laser scribing graphene are fabricated. The outlook and challenges of laser scribing technology have also been discussed. Laser scribing may be a potential way of fabricating wearable and integrated graphene systems in the future.